Development and Evaluation of Phenytoin Loaded Chitosan Nanoparticles using Different Formulation Methods for Anti-epileptic and Intranasal Delivery Applications - نتوف, عبد الكريم; كفى, همام; يوسفان, أمل (Latakia University Journal -Medical Sciences Series, 2021)
In recent years, attention has been given to polymeric nanoparticles as promising drug delivery systems through the vital mucus and the development of several drug delivery systems to the brain, including chitosan nanoparticles because of their advantages, which are the bio-adhesive properties. The aim of the presented study focuses on preparing chitosan nanoparticles and evaluating the properties of the resulting particles according to the encapsulation efficiency and resulting dimensions. The methods of ionic cross linking, emulsification with solvent diffusion and evaporation, and nanopricipitation methods were employed to produce the nanoparticles. The nanopricipitation method based on adding organic phase contained lecithin and phenytoin to the chitosan solution in aqueous medium showed the greatest encapsulation efficiency (EE%) reaching 67% with dimensions of 311.3nm. These results are preliminary, but they are promising for determination of manufacturing conditions to reach the best physicochemical properties of the prepared particles and to study their effectiveness in brain targeting after being administrated via the nasal route.